2022
DOI: 10.32604/iasc.2022.027146
|View full text |Cite
|
Sign up to set email alerts
|

End-to-end Handwritten Chinese Paragraph Text Recognition Using Residual Attention Networks

Abstract: Handwritten Chinese recognition which involves variant writing style, thousands of character categories and monotonous data mark process is a longterm focus in the field of pattern recognition research. The existing methods are facing huge challenges including the complex structure of character/line-touching, the discriminate ability of similar characters and the labeling of training datasets. To deal with these challenges, an end-to-end residual attention handwritten Chinese paragraph text recognition method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…This work presents a hybrid deep learning model that uses a convolutional neural network (CNN) and a bidirectional short-term memory network (BLSTM) and it operates without requiring segmentation. Primarily, CNN and RNN algorithms have been widely used for text recognition [4]. Several studies have shown that convolutional neural networks and recurrent neural networks (RNNs) are superior to Hidden Markov Models (HMMs) for sequence labeling tasks such as handwriting and speech recognition [5] in addition, RNN long-term short-term memory (LSTM) architecture allows it to capture longer contexts, which are important for the recognition of offline text tasks.…”
Section: Introductionmentioning
confidence: 99%
“…This work presents a hybrid deep learning model that uses a convolutional neural network (CNN) and a bidirectional short-term memory network (BLSTM) and it operates without requiring segmentation. Primarily, CNN and RNN algorithms have been widely used for text recognition [4]. Several studies have shown that convolutional neural networks and recurrent neural networks (RNNs) are superior to Hidden Markov Models (HMMs) for sequence labeling tasks such as handwriting and speech recognition [5] in addition, RNN long-term short-term memory (LSTM) architecture allows it to capture longer contexts, which are important for the recognition of offline text tasks.…”
Section: Introductionmentioning
confidence: 99%